2023
DOI: 10.1002/sstr.202200285
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Enhanced Conversion of CO2 to Light Olefins: Basis in Thermal Catalysis, Current Progress, and Future Prospects

Abstract: Carbon dioxide (CO2) valorization to light olefins via sustainable energy input poses great industrial significance for the synthesis of key chemical feedstocks and reduces emission of this potent greenhouse gas. Solar energy, harnessed using light‐capturing catalytic materials, can negate external heat requirements for the energy‐intensive reaction. Presently, photothermal CO2‐Fischer–Tropsch synthesis (FTS)‐dedicated studies remain limited and are focused on the nonselective synthesis of C2+ hydrocarbons. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 188 publications
0
6
0
Order By: Relevance
“…The other option is to design new hybrid systems of photovoltaic and photocatalytic devices, allowing solar energy to be successfully utilized for more extended periods of time, and perhaps combine emergent technologies such as external stimuli technologies, such as magnetic, , mechanical, or thermal. , In the future, hybrid photoreactor architecture appears to be a promising solution for the year-round production of solar fuel and offers much more consideration, with tremendous potential impact on society and space exploration. , Consequently, by combining solar cells with a photoreactor system, it is possible to carry out efficient and affordable heterogeneous photocatalytic processes.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…The other option is to design new hybrid systems of photovoltaic and photocatalytic devices, allowing solar energy to be successfully utilized for more extended periods of time, and perhaps combine emergent technologies such as external stimuli technologies, such as magnetic, , mechanical, or thermal. , In the future, hybrid photoreactor architecture appears to be a promising solution for the year-round production of solar fuel and offers much more consideration, with tremendous potential impact on society and space exploration. , Consequently, by combining solar cells with a photoreactor system, it is possible to carry out efficient and affordable heterogeneous photocatalytic processes.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…The reverse water gas shi (RWGS) reaction hydrogenates CO 2 into CO, which can be further used to synthesize methanol, breaking through the thermodynamic equilibrium limit of direct methanol production from CO 2 , 10,11 and can also be combined with Fischer-Tropsch synthesis (FTS) process to prepare useful chemicals such as olens. [12][13][14][15] Whether producing methanol through the CAMERE method (carbon dioxide hydrogenation to form methanol via a RWGS reaction) or preparing low-carbon olens via the CO 2 -FTS method, the RWGS reaction with high CO yield is a crucial step. Therefore, the RWGS reaction is considered as the most promising and prospective pathway in re-utilizing CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…30−32 The strategic integration of photocatalytic processes with thermocatalytic mechanisms, a burgeoning field of research, has the potential to augment the overall catalytic performance synergistically. [11][12][13]28,33 The advancement of light-involved olefin production has been demonstrated in the process of ethane and propane dehydrogenation, methane coupling, and CO x reduction via H 2 or H 2 O. Several reviews have reported the catalysis and mechanism in thermal catalytic olefin synthesis and light-invovled CO x hydrogenation to various products (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Light olefins can be synthesized from diverse feedstocks, including hydrocarbon sources like crude oil, natural gas, and shale gas, as well as oxygenates such as biomass, organic waste, and methanol, as listed in Table . In recent years, CO and CO 2 have also emerged as significant raw materials for light olefins synthesis, reflecting a broader trend toward sustainability and carbon utilization. Traditional cracking and Fischer–Tropsch processes for producing light olefins are energy-intensive and heavily reliant on fossil fuels, emitting approximately 400 million tons of CO 2 each year . Thus, the efficiency, selectivity, stability, and environmental compatibility in olefin production have been increasingly prioritized.…”
Section: Introductionmentioning
confidence: 99%